2018
DOI: 10.1002/ejsp.2362
|View full text |Cite|
|
Sign up to set email alerts
|

Living under threat: Mutual threat perception drives anti‐Muslim and anti‐Western hostility in the age of terrorism

Abstract: This research demonstrates a common psychology of outgroup hostility driven by perceived intergroup threat among three groups and seven cultural contexts: non‐Muslim Westerners, Muslims in Western societies, and Muslims in the Middle East. In Study 1, symbolic, but not realistic and terroristic threats, predicted non‐Muslim Norwegians' intentions to join anti‐Islamic movements. In Study 2, symbolic and realistic, but not terroristic threat, predicted non‐Muslim Americans' willingness to persecute Muslims. In S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
111
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(130 citation statements)
references
References 69 publications
7
111
0
1
Order By: Relevance
“…Hence, we merged threat from terrorism with the more general safety threat category. Previous research has shown that terrorist threat is strongly associated with prejudice (e.g., Cohrs et al., ; Doosje et al., ; Obaidi et al., ; Uenal, ). However, explicit concerns about terrorism seem to play only a minor role in the current context of refugee migration.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Hence, we merged threat from terrorism with the more general safety threat category. Previous research has shown that terrorist threat is strongly associated with prejudice (e.g., Cohrs et al., ; Doosje et al., ; Obaidi et al., ; Uenal, ). However, explicit concerns about terrorism seem to play only a minor role in the current context of refugee migration.…”
Section: Resultsmentioning
confidence: 98%
“…Perceived threat predicts prejudice better than objective measures of threat (Stephan, Ybarra, & Rios Morrison, 2009). The threat types outlined above (e.g., symbolic, realistic, and safety threat) predict attitudes towards out-groups to a similar extent (e.g., Doosje et al, 2009;Esses et al, 2013;Obaidi et al, 2018;Riek et al, 2006;Uenal, 2016;Yitmen & Verkuyten, 2018). Yet, research points to differences between individual threats (e.g., threat to one's own job) and group-based threats (e.g., threat to the economy that affects the whole in-group): Groupbased threats tend to be more strongly associated with prejudice and discrimination (Maoz & McCauley, 2005;Onraet, Van Hiel, Dhont, & Pattyn, 2013) for those who strongly identify with their in-group (Bizman & Yinon, 2001;Tausch, Hewstone, Kenworthy, Cairns, & Christ, 2007).…”
Section: Thre At T Ype S and At Titude Smentioning
confidence: 95%
See 1 more Smart Citation
“…As social, political, and technological changes in our societies have apparently accelerated in recent years, there has been a corresponding increase in research that aims to understand social change (see Figure 1). For example, social psychological science has made good progress in explaining why people engage in social change-related behaviours such as collective action (see van Zomeren, Kutlaca, & Turner-Zwinkels, 2018); intergroup conflict (e.g., Obaidi, Kunst, Kteily, Thomsen, & Sidanius, 2018;Tajfel & Turner, 1979); the contestation of unequal status relations (e.g., Brown-Iannuzzi, Lundberg, Kay, & Payne, 2015;Haslam & Reicher, 2006); and recovery from conflict (e.g., Iqbal & Bilali, 2018;McKeown & Taylor, 2018) and/or disaster (Drury, Brown, Gonz alez, & Miranda, 2016). However, there has been much less research in psychology that aims to explain the origins and consequences of change at a macro, societal level (Figure 1).…”
mentioning
confidence: 99%
“…An analysis of perceptions of threat among Protestants, Catholics, Jews and Muslims in the United States suggested that greater perception of threats toward one's religious identity was linked to more negative outgroup attitudes among Protestants, Catholics, and Jews (Pasek and Cook, 2018). Threats from Muslims toward Norwegian and American Christian identities have been linked to support for collective action against Muslim immigrants (Study 1 and Study 2; Obaidi et al, 2018) and threats toward Muslim identity were associated with anti-Western hostilities (Study 3 and 4; Obaidi et al, 2018). Similar results were found in a study assessing reactions to threats towards one's gender and national identities (Fischer et al, 2010), suggesting that this process is not an inherent aspect of religion, but an aspect of social identities in general.…”
Section: Threats To Social and Religious Identitymentioning
confidence: 99%